Centenary of the Central Building of the Faculty of Medicine of San Marcos University - PAMO, OSCAR G. (2004)
On September 6, 1903, the main building of the current Faculty of Medicine of San Marcos University was inaugurated with its frontispiece facing Grau Avenue and next to Lima’s Botanical Garden. This new building replaced the old one located at Santa Ana’s Square, then Italia’s Square and now Raimondi’s Square, in Cercado de Lima suburb, where the Royal College of Physicians and Surgeons of San Fermando functioned since 1808 and later the Faculty of Medicine of Lima since 1856. The decision to create this new building was due to President Pierola’s rule in 1897, the work was started in 1899 and inaugurated by President Romaña.